2008
DOI: 10.1093/jxb/ern107
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous PttHb1 and PttTrHb, and heterologous Vitreoscilla vhb haemoglobin gene expression in hybrid aspen roots with ectomycorrhizal interaction

Abstract: Present knowledge on plant non-symbiotic class-1 (Hb1) and truncated (TrHb) haemoglobin genes is almost entirely based on herbaceous species while the corresponding tree haemoglobin genes are not well known. The function of these genes has recently been linked with endosymbioses between plants and microbes. In this work, the coding sequences of hybrid aspen (Populus tremula×tremuloides) PttHb1 and PttTrHb were characterized, indicating that the key residues of haem and ligand binding of both genes were conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 59 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…NsHb1 is involved in various biotic and abiotic stress responses. For example, nsHb1 genes have been reported to be up-regulated by hypoxic, osmotic, and high salt 6 10 11 , short-term waterlogging 12 , treatments with salicylic acid, methyl jasmonic acid, ethylene, and H 2 O 2 13 , deficiency of phosphorus, potassium, and iron 8 , as well as dual culture with specific microsymbionts 14 . NsHb1 genes were also strong induced by nitrate, nitrite, or nitric oxide (NO) 15 16 .…”
mentioning
confidence: 99%
“…NsHb1 is involved in various biotic and abiotic stress responses. For example, nsHb1 genes have been reported to be up-regulated by hypoxic, osmotic, and high salt 6 10 11 , short-term waterlogging 12 , treatments with salicylic acid, methyl jasmonic acid, ethylene, and H 2 O 2 13 , deficiency of phosphorus, potassium, and iron 8 , as well as dual culture with specific microsymbionts 14 . NsHb1 genes were also strong induced by nitrate, nitrite, or nitric oxide (NO) 15 16 .…”
mentioning
confidence: 99%
“…The bacterial hemoglobin (VHb) from the obligate aerobic bacterium Vitreoscilla is an oxygen-binding protein, functioning as an oxygen carrier and transporter (Wakabayashi et al 1986 ). In bacteria (Horng et al 2010 ), yeasts (Wu and Fu 2012 ), plants (Jokipii et al 2008 ) and animals (Pendse and Bailey 1994 ), the introduction of VHb has been proven to efficiently facilitate cellular aerobic metabolism, by which the growth rate and protein synthesis are improved under oxygen-limited conditions. Recently, examples have demonstrated that this strategy also works well in filamentous fungi.…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous results, the PttTrHb expression was enhanced in roots of hybrid aspen ( Populus tremula L. × tremuloides Michx.) dual-cultured with ectomycorrhizal fungi [16] .…”
Section: Introductionmentioning
confidence: 99%
“…As bacterial TrHbs are known to detoxify NO [24] , Vieweg and co-authors [13] proposed that, similarly, the MtTrHb1 and MtTrHb2 proteins of M. truncatula (Mtr-HbO) could suppress NO accumulation during nodule and mycorrhizal symbioses. In our previous paper, we suggested that in hybrid aspen, PttTrHb may be involved in the modulation of NO levels in early reactions involved in root growth, in response to symbiosis with the ectomycorrhizal fungi [16] . In an A. thaliana mutant, the lack of the Ath-HbO protein inhibited the germination of seeds at elevated temperatures where the NO lifetime was increased and the germination restored with the addition of an NO scavenger, which suggests a potential role for TrHb as an NO scavenger [25] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation